Mendelian inheritance, genetic linkage, and genotypic disequilibrium for nine microsatellite loci in Cariniana estrellensis (Raddi) Kuntze (Lecythidaceae) - Kubota, T. Y. K. [UNESP]; Silva, A. M. [UNESP]; Cambuim, J. [UNESP]; Silva, A. A. [UNESP]; Pupin, S. [UNESP]; Silva, M. S. [UNESP]; Moraes, M. A. [UNESP]; Moraes, M. L. T. [UNESP]; Sebbenn, A. M. (Funpec-editora, 2017)
Cariniana estrellensis is one of the largest trees found in Brazilian tropical forests. The species is typical of advanced stages of succession, characteristic of climax forests, and essential in genetic conservation and environmental restoration plans. In this study, we assessed Mendelian inheritance, genetic linkage, and genotypic disequilibrium in nine microsatellite loci for a C. estrellensis population. We sampled and genotyped 285 adult trees and collected seeds from 20 trees in a fragmented forest landscape in Brazil. Based on maternal genotypes and their seeds, we found no deviation from the expected 1: 1 Mendelian segregation and no genetic linkage between pairwise loci. However, for adults, genotypic disequilibrium was detected for four pairs of loci, suggesting that this result was not caused by genetic linkage. Based on these results, we analyzed microsatellite loci that are suitable for use in population genetic studies assessing genetic diversity, mating system, and gene flow in C. estrellensis populations.
Keywords: Forest fragment; Genetic conservation; Jequitiba-branco; Population genetics; Tropical trees